Characterisation of composite-titanium alloy hybrid joints using digital image correlation. (15th April 2016) - Wang, Xichang; Ahn, Joseph; Kaboglu, Cihan; Yu, Long; Blackman, Bamber R.K.
Abstract: An advanced Comeld hybrid joining technology for joining Ti6Al4V and carbon fibre reinforced polymer (CFRP) is presented. The Comeld joining method utilises protrusions formed on the surface of the metal by electron beam surface treatment which are then embedded into composite layers to form an integrated joint by co-curing. In this paper, joints were formed with wedge profiled protrusions on the metal surface and during tensile testing the protrusions resisted fracture in all tests, leading to failure in the composite part. A digital image correlation (DIC) technique was used to monitor full field, in-plane strain during the tests and to also identify the development of failure modes. The results from specimens with protrusions exposed on the side surface by grinding showed that the embedded protrusions are effective in reducing stress concentration near the metal composite interface and therefore contributed to improved mechanical properties of the hybrid joints.